Gravity survey of the central Alpine Fault near the DFDP-2 drill site, Whataroa, South Island, New Zealand. Issue 1 (2nd January 2020) - Jenkins, Steve; Sutherland, Rupert; Townend, John
ABSTRACT: We present a high-precision gravity survey of the Whataroa River valley near the DFDP-2 drill site. We measured 466 new sites and achieved a standard error on repeat measurements of 0.015 mGal. We combined existing data from 134 sites. A negative residual gravity anomaly of up to 6 mGal is interpreted as a buried glacial channel 350–450 m beneath the valley floor. It is apparently dextrally offset and upthrown to the southeast by the Alpine Fault. We are able to better constrain the surface trace location of the Alpine Fault by combining gravity models with surface mapping. A high horizontal gravity gradient near the DFDP-2 drill site requires a steeply-dipping or overhanging bedrock surface, and indicates that an active reverse fault might bound the base of the hillslope. A 4 mGal residual gravity minimum near the axis of the valley near the DFDP-2 drill site is interpreted as the deepest point upstream of the fault of what was a lake that formed at the end of the Last Glacial Maximum (∼18 ka).